The Effect Of Work Supervision And Non-Physical Work Environment On The Performance Of Employees At Avsec Unit Pt Angkasa Pura Ii (Persero) Hang Nadim Airport Branch Batam - Agus Fati Wijaya; Erma Kurnia; Haji Mustaqim (International Journal of Business and Quality Research, 2023)
This study aims to determine the effect of work supervision and non-physical work environment on the performance of employees of the Avsec unit of PT Angkasa Pura II (Persero) Hang Nadim Airport Batam Branch. The sample in this study were all permanent employees at the AVSEC Unit, totaling 68 people. Sampling using census technique. Data collection techniques in this study were interviews and questionnaires with data analysis using descriptive methods and using multiple regression. The conclusion obtained is that partially work supervision has a significant effect on the performance of employees of the AVSEC Unit of PT Angkasa Pura II (Persero) Branch of Hang Nadim Airport Batam. Partially, the non-physical work environment has a significant effect on the performance of employees of the AVSEC Unit of PT Angkasa Pura II (Persero) Hang Nadim Airport Batam Branch. Simultaneously work supervision and non-physical work environment have a significant effect on the performance of employees of the AVSEC Unit of PT Angkasa Pura II (Persero) Hang Nadim Airport Batam Branch. R2 value of 0.692. This means that the contribution of the influence of supervision and work environment variables to the performance variable is 69.2% while the remaining 30.8% is influenced by other variables not included in this study.